2011
DOI: 10.1007/s00701-011-1003-8
|View full text |Cite
|
Sign up to set email alerts
|

Cooled radiofrequency application for treatment of sacroiliac joint pain

Abstract: It was seen that the cooled radiofrequency used for sacroiliac denervation was an effective and safe method in the short to intermediate term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 23 publications
0
39
0
3
Order By: Relevance
“…Also it is impossible to elicit an objective response by the electrical nerve stimulation, such as muscle contractions in localising a motor nerve. Cooled RF is a novel technology whereby internally cooled RF probes can reportedly yield larger tissue lesions than those created by standard RF probes [7].…”
Section: Discussionmentioning
confidence: 99%
“…Also it is impossible to elicit an objective response by the electrical nerve stimulation, such as muscle contractions in localising a motor nerve. Cooled RF is a novel technology whereby internally cooled RF probes can reportedly yield larger tissue lesions than those created by standard RF probes [7].…”
Section: Discussionmentioning
confidence: 99%
“…from Turkey in 2011 found similar pain relief in >80% of patients after 6 months of neurotomy. [8] In the subsequent year, Patel et al . conducted a randomized placebo-controlled trial among 51 patients (34 patients received cooled RF intervention) and observed significant pain relief and better quality of life for 9 months in those who had WC-RF based neuroablation.…”
Section: Discussionmentioning
confidence: 99%
“…Karaman et al [8] провели анализ результатов моно-полярной радиочастотной нейроабляции охлаждае-мым электродом дорсальной ветви L 5 и латеральных веточек S 1 -S 3 у 14 пациентов. Авторы отметили значи-тельное снижение боли и улучшение качества жизни сроком более чем на 6 мес.…”
Section: îáñóAeäåíèåunclassified